Transformation of Bima local wisdom values through social studies e-book media - Ardiansyah, Suriadi; Komalasari, Kokom; Maryani, Enok; Wiyanarti, Erlina (Journal of Education and Learning (EduLearn), 2024)
The development of postmodern-era technology in the world of education is increasingly sophisticated, thus impacting the character of students and their social environment. Technological progress negatively affects the lives of today's generation. When misuse of technology is widespread, it is imperative to strengthen cultural and religious filtration. So that the influence of globalization on technological development can be minimized. So as not to damage the cultural values and morality of students as the next generation of the nation. This study aims to explain the importance of transforming the values of Bima's local wisdom "Nggusu Waru" through the media of social studies e-books. The results and conclusions of this study are efforts to develop students' social character that require teacher collaboration, supervision, and optimal parental attention so that their interest in learning is higher and minimizes deviant behavior. This research method uses research and development design. At the stage of preliminary studies with models developed by Borg and Gall. Through several stages of research, information gathering, development of initial forms of products, and initial field testing. In this step, data is collected through interviews, observation and documentation. The data is analyzed to find out some of its weaknesses and shortcomings.